Nutrient analysis and acceptability of different ratio pearl millet (Pennisetum glaucum) based biscuits - singh, ritu; nain, M s; manju, manju (The Indian Journal of Agricultural Sciences, 2020)
Biscuits being important food snacks for children and adults are rich in fat and sugar content than whole bread. Lower contents of proteins (lysine), vitamins and dietary fibers are the nutritional problems with most bakery products clamoured interest in increasing the nutrients and fiber content in the biscuits. Pearl millet (Pennisetum glaucum) has received considerable attention for their high content of dietary fibres, phytochemicals and nutritional value. On farm trial was conducted in the South West district of Delhi during rabi 2014–15, 2015–16 and 2016–17 among 30 farm women with three treatments with an objective to prepare biscuits with partial replacement of wheat flour with different proportions of pearl millet flour and to study its acceptability and nutritive value among farm women. The developed biscuits were sensory evaluated using nine point hedonic scale and evaluated for nutritive value in terms of carbohydrate, protein, fat, fiber, calcium and iron. Results showed that biscuit prepared with chick pea floor was highly acceptable whereas already established practice was least acceptable. The nutrient analysis showed highest protein; fat; carbohydrate; dietary fiber; calcium and iron in chick pea biscuit sample i.e. 16.25%; 45.36%; 75.25%; 13.53%; 41.33% and 6.53%, respectively. Replacement of wheat flour with pearl millet flour and chick pea flour increased the protein, fibers and iron contents proportionately to the level of substitution. Chick pea flour made biscuit was found most acceptable and was much appreciated when compared with other two types of biscuits among farm women.